Towards Citation Justice: Ensuring an Inclusive Search and Literature Retrieval: A Western Librarian's Perspective - Ruiter, Floor Agnes Andrea (KULA)

(untitled) (University of Victoria Libraries, 2026)
The main sources of citation injustice are the collective biases in the scientific community, including literature retrieval bias, which has direct effects on citation inequality. In this commentary I focus on index bias in literature databases, inherent/unconscious bias during search strategy development, and systematic bias of controlled vocabularies. Exemplar literature search strategies and/or retrieval analyses comparing Web of Science and OpenAlex are used to demonstrate these biases. Moreover, this commentary offers steps to consider during literature search preparation, search query building, and the search itself, which can lead to a more inclusive representation of the literature in the topic of interest and reduce citation inequity.